Implementation Of Local Wisdom-Based Stem Integrated PBL Learning Devices (Gasingan) To Improve Students' Creative Thinking Skills - Zen, Fadhila Zilfa; Pathoni, Haerul; Amnie, Erlida (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2025)
This study aims to investigate the effectiveness of implementing STEM-integrated Problem-Based Learning (PBL) instructional tools based on local wisdom (Gasingan) in improving students' creative thinking skills on the topic of rotational dynamics at SMA Negeri 11 Kota Jambi. The research employed a quantitative approach using a quasi-experimental design with a non-equivalent control group, involving an experimental class and a control class. The experimental class received STEM-integrated PBL learning, while the control class was taught using conventional methods. Both groups were given pretests and posttests to measure students’ creative thinking skills. Data were analyzed using SPSS and manual calculations via Microsoft Excel. The results showed a significant increase in students’ creative thinking skills in the experimental class, as indicated by the Paired Sample T-test with a significance value of 0.000 (p < 0.05). The improvement was greater than in the control class, suggesting that the use of STEM-integrated PBL tools enriched with local wisdom positively impacted students' engagement and cognitive development in learning physics, particularly in understanding rotational dynamics concepts.